Portuguese hosts for Ornithodoros erraticus ticks - Palma, Mariana (2013)
The hematophagous soft tick Ornithodoros erraticus feeds nocturnally on multiple warm-blooded vertebrate hosts. This tick is often found living buried in the soil of traditional pigpens. O. erraticus is an important infectious disease vector both for humans and animals. In the Iberian Peninsula, this tick serves as the vector of human tick-borne relapsing fever caused by the spirochete Borrelia hispanica. The natural ecosystems maintaining this spirochete are not well understood, with details of competent vertebrate reservoirs and tick–host interactions poorly understood. Investigation of arthropod blood meal composition provides evidence linking the vector to specific hosts, providing insights into possible disease reservoirs. Ticks collected from two pigpens located in southern Portugal were subjected to blood meal analysis. PCR amplification of vertebrate cytochrome b was used to disclose the original host from which 349 ticks had derived their previous blood meal. Host origins for blood meal analysis from 79 of 349 ticks revealed that 46.8% had previously fed from pigs, 35.4% human, 13.9% bovine, 5.1% sheep, 1.3% rodent, and 1.3% from birds. Three samples revealed mixed blood meals, namely, human–pig (1.3%), sheep–pig (1.3%), and bovine–pig (1.3%). The major role of pigs as hosts is consistent with fieldwork observations and underlines the importance of pigs for maintaining O. erraticus tick populations. Humans serve as accidental hosts, frequently confirmed by reports from both producers and veterinarians. Other livestock species and wildlife prevalent in the region appear only to have a minor role in maintaining this tick. The results demonstrate the importance of blood meal analysis to determine tick hosts providing a tool for investigation of sylvatic cycle for Borrelia hispanica.